The side effects of clobazam as add-on therapy in pediatric epilepsy patients - Bilge, Serap; Taşkın, Sema Nur; Başkaya, Nevzat (The European Research Journal, 2025)
Objectives: Epilepsy is a long-term cerebral disorder that accompanies a lifelong predisposition to epileptic seizures, resulting in neurobiological, cognitive, psychological, and social problems. Clobazam is considered a relatively safe and effective anticonvulsant, frequently prescribed for the management of pediatric epilepsy. This study was designed to rigorously evaluate the safety profile of clobazam in pediatric epilepsy, with a particular focus on the incidence and nature of treatment-emergent side effects. Methods: Patients aged 2 to 17 years, who received clobazam as an adjunct to valproic acid, levetiracetam, or carbamazepine therapy, who were referred to Diyarbakır Children’s Hospital between December 2021 and March 2023 were included. We evaluated the safety profile of clobazam in pediatric epilepsy, with a particular focus on the incidence and nature of treatment-emergent side effects. Results: The study included 100 patients using clobazam as an add-on anti-seizure medication. The mean age was 11.0±4.0 years, with males comprising 48% of the cohort. The average duration of clobazam use was 16.3±7.2 months. Side effects were reported in 30 patients (30%), with the most common being insomnia (10%), agitation (9%), and somnolence (6%). Allergic reactions were the least frequent. No patients experienced enuresis, ataxia, hypertension, hypotension, or constipation in our study. Clobazam was discontinued by 12% of the patients due to side effects. Conclusions: Clobazam is regarded as safe in pediatric epilepsy patients, with minimal concerns regarding drug interactions and adverse reactions. Although it may cause some side effects, initiating low-dose treatment and gradually increasing the dosage can enhance treatment success.